Synthesis of Double-Walled Boron Nitride Nanotubes from Ammonia Borane by Thermal Plasma Methods - Bae, Dongsu; Jung, Unseok; Lee, Hunsu; Yoo, Heeil; Moon, Se Youn; Lee, Kun-Hong; Kim, Myung Jong (ACS Publications, 2023)
Highly crystalline double-walled boron nitride nanotubes(DWBNNTs similar to 60%) were synthesized from ammonia borane (AB; H3B-NH3) precursors using a high-temperature thermalplasma method. The differences between the synthesized BNNTs usingthe hexagonal boron nitride (h-BN) precursor and AB precursor werecompared using various techniques such as thermogravimetric analysis,X-ray diffraction, Fourier transform infrared spectroscopy, Ramanspectroscopy, scanning electron microscopy, transmission electronmicroscopy, and in situ optical emission spectroscopy (OES). The synthesizedBNNTs were longer and had fewer walls when the AB precursor was usedthan when the conventional method was used (with the h-BN precursor).The production rate significantly improved from similar to 20 g/h (h-BNprecursor) to similar to 50 g/h (AB precursor), and the content of amorphousboron impurities was significantly reduced, implying a self-assemblymechanism of BN radicals rather than the conventional mechanism involvingboron nanoballs. Through this mechanism, the BNNT growth, which wasaccompanied by an increased length, a decreased diameter, and a highgrowth rate, could be understood. The findings were also supportedby in situ OES data. Considering the increased production yield, thissynthesis method using AB precursors is expected to make an innovativecontribution to the commercialization of BNNTs.